Comparative study of the antibacterial and anti-inflammatory activities of the seed coat vs. seed kernel extracts from the plant Mangifera indica L. in inflammatory acne treatment - Ngoc Nha Thao Nguyen; Duc Linh Vo; Duy Khanh Dang; Trung Hieu Huynh; Cao Thien Ha (Shahrekord University of Medical Sciences, 2023)
Introduction: The present study was developed to investigate and compare the extraction yield, the contents of polyphenols and mangiferin, the activities against Propionibacterium acnes, Staphylococcus aureus, and Escherichia coli bacteria, and the anti-inflammatory activities of ethanol extracts of mango seed kernels vs. seed coats. Methods: Mango seed kernels and seed coats were extracted using ethanol as the solvent and tested against microorganisms using the disc diffusion method. The minimum inhibitory concentration (MIC) levels of extracts were determined by the agar dilution method. The anti-inflammatory activities were assessed both in vitro and in vivo by albumin denaturation method and carrageenan-induced paw edema test, respectively. Results: Both extracts yielded high contents of mangiferin and phenolic compounds. The antibacterial activities of both extracts showed inhibition of the tested microorganisms Propionibacterium acnes and Staphylococcus aureus but not Escherichia coli. Seed kernel extract (0.2 g/kg) reduced paw edema by 44.8% at 3 hours after λ-carrageenan administration. Meanwhile, 0.5 g/kg seed coat extract reduced paw edema less than the seed kernel extract (23.1% vs. 44.8%). Mango seed kernel extract, mango seed coat extract, and diclofenac sodium displayed concentration-dependent inhibition of heat-induced protein denaturation with IC50 values of 137.23 μg/mL, 292.12 μg/mL, and 6.64 μg/mL, respectively. Conclusion: The obtained results confirmed the antibacterial and anti-inflammatory potential of mango seed kernel and seed coat extracts. The mango seed kernel extract was proven to be more effective than the mango seed coat extract and thus can be used in cosmetics as an anti-inflammatory and antibacterial agent.